2009
DOI: 10.1007/s00412-009-0245-1
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal and telomeric reprogramming following ES-somatic cell fusion

Abstract: Chromosomal and telomeric reprogramming was assessed in intraspecies hybrids obtained by fusion of embryonic stem (ES) cells and mouse embryonic fibroblasts. Evaluation of the ploidy of ES-somatic hybrids revealed that 21 of 59 clones had a tetraploid DNA profile while the remaining clones showed deviations from the expected profile of fusion between two diploid cells. Microsatellite polymerase chain reaction analysis of four of these clones demonstrated no random loss of somatic chromosome pairs in the ES-som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…This is due to the repression of telomerase during differentiation which coincides with telomere shortening, which can ultimately lead to replicative senescence (Osterhage and Friedman, 2009). It has previously been shown that telomerase activity and telomere lengthening occurs following reprogramming by SCNT (Tian et al, 2000;Wakayama et al, 2000), the induction of pluripotency by transcription factors (Marion et al, 2009;Takahashi and Yamanaka, 2006) and ES-somatic cell fusion (Cowan et al, 2005;Sumer et al, 2010b). In the present study we report that the length of telomeres and levels of telomerase activity appeared to be restored to pluripotent stem cell levels in both ES-somatic and iPS-somatic cell hybrids.…”
Section: Rt-pcrsupporting
confidence: 63%
See 3 more Smart Citations
“…This is due to the repression of telomerase during differentiation which coincides with telomere shortening, which can ultimately lead to replicative senescence (Osterhage and Friedman, 2009). It has previously been shown that telomerase activity and telomere lengthening occurs following reprogramming by SCNT (Tian et al, 2000;Wakayama et al, 2000), the induction of pluripotency by transcription factors (Marion et al, 2009;Takahashi and Yamanaka, 2006) and ES-somatic cell fusion (Cowan et al, 2005;Sumer et al, 2010b). In the present study we report that the length of telomeres and levels of telomerase activity appeared to be restored to pluripotent stem cell levels in both ES-somatic and iPS-somatic cell hybrids.…”
Section: Rt-pcrsupporting
confidence: 63%
“…2A). Furthermore, the cell cycle profiles of the two hybrid lines were shown to be similar to that of ES and iPS ous data (Sumer et al, 2010b), increased telomere fluorescence intensity was observed in ES cells compared to MEFs, with ES cell telomeres an average of 2.3 times longer than the MEF cell line telomeres. Similarly the induction of pluripotency of the QS MEFs resulted in iPS cells with a mean telomere fluorescence 2.5 fold longer following reprogramming (Fig.…”
Section: Characterization Of Cell Hybridsmentioning
confidence: 59%
See 2 more Smart Citations
“…Telomere repeat amplification protocol assays and telomere length analysis were performed as previously described (44) with minor modifications (45,46).…”
Section: Methodsmentioning
confidence: 99%